Do great cases make bad law? - Bloom, Lackland H., Jr. (New York : Oxford University Press, 2014)
Justice Holmes proclaimed that 'great cases, like hard cases make bad law'. He explained that this was so because the 'hydraulic pressures' of the great case tend to distort the judgements of the justices. The purpose of this book is to examine 25 great cases that arose throughout the history of the Supreme Court and to attempt to determine whether Holmes was correct. More particularly, the book discusses the impact that the greatness of the case may have had on its presentation to the Court, the Court's deliberations, the decision, the opinion and the law that was created.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: United States. -- Supreme Court; Constitutional law -- United States -- Cases; Political questions and judicial power -- United States -- Cases